Approximation of compressions of periodic functions in the space $L_p,\; p < 1$ - Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Behavior of the best approximation of function compressions by trigonometric polynomials in $L_p,\; p < 1$ is investigated.